ALUR TOKOH DAN PENOKOHAN LATAR NOVEL DAN FILM ANCIKA DIA YANG BERSAMAKU KAJIAN EKRANASI - Winda Waromah; Helmi Seftiani; Dwi Setiyawan (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This research explores the process of ekranisasi the adaptation of literary works into cinematic form through a comparative analysis of the novel "Ancika Dia yang Bersamaku 1995" by Pidi Baiq and its 2024 film adaptation directed by Benni Setiawan. The study focuses on the transformation of intrinsic narrative elements, namely plot, characters and characterization, and setting. Employing a qualitative descriptive method and content analysis, this research examines the narrative shifts that occur during adaptation using the framework of ekranisasi, which includes three key aspects: reduction, addition, and modification. The findings indicate significant changes in character representation, scene construction, and setting transitions between the two mediums. While some elements from the novel were omitted or altered due to the constraints and demands of cinematic storytelling, other components were creatively added to enhance audience engagement. These transformations highlight the interpretive nature of film as a distinct artistic medium and emphasize the need to consider both the limitations and potentials of adaptation. The study contributes to comparative literature and film studies, offering critical insight into how narrative meaning is negotiated, restructured, and reimagined in the adaptation process within the Indonesian cultural context.